An interprofessional examination of the Johns Hopkins Mobility Goal Calculator among hospitalized postsurgical patients. (12th August 2022) - McLaughlin, Kevin H.; Young, Daniel; Friedman, Lisa A.; Peters, Jessica; Vickery, Gina; Hoyer, Erik H.
Abstract: Individualized mobility goals created using a goal calculator have been shown to increase patient mobility on medical nursing units, but have not been studied among postoperative populations. This study aimed to examine the feasibility of an automated mobility goal calculator on a postoperative nursing unit. To examine this, we used the goal calculator to create goals for patients ( N  = 128) following surgery and mobilized each patient with either a nurse or physical therapist. Each patient's highest level of mobility was recorded and providers completed surveys on the appropriateness of calculated goals. Overall, 94% of patients achieved calculated goals. Patients with more pain achieved goals significantly less often than those with less pain. Those with higher mobility achieved their goals similarly with either provider. Providers reported 47% of goals were appropriate, with goals being set too low as the primary reason for goals being inappropriate. We conclude that the automated goal calculator can be used on postoperative nursing units to set realistic goals for patients after surgery.